An evaluation of the discriminatory power of selected Polish bankruptcy prediction models as part of the validation process - Nehrebecka, Natalia (Ocena siły dyskryminacyjnej wybranych polskich modeli predykcji bankructwa w ramach procesu walidacji, 2018)
The purposes of this article are to present validation techniques according to their discriminatory power, while indicating the reservations about such techniques, and to check the adjustment of the existing Polish bankruptcy prediction models in the context of their discriminatory power. This is the first study that performs a validation of such models. Based on the analysis, it was found that the fifth model developed by Hadasik was characterised by a very high discriminatory power. The decision was made to base the evaluation of the discriminatory power of the modules on the Gini index, the Kolmogorov-Smirnov statistic, the H measure, the information value (IV), and the precision of the estimates of bankruptcy
Financial Sciences. Nauki o Finansach, 2018, vol. 23, no. 4, s. 63-88
Keywords: bankruptcy prediction; discriminatory power; validation